Selección de factores clave en el rendimiento de biomasa de Kluyveromyces fragilis a partir de suero de queso usando un diseño Placket-Burman. - Oblitas, J. (2020)
In this work a study of biomass production from deproteinized serum of cheese was made by using yeast Kluyveromyces fragilis from the Spanish Type Culture Collection with the objective of providing an alternative of use for the subproduct “serum of cheese”, since this product is highly pollutant. Ammonium salts, potassium, magnesium, calcium, iron, zinc and manganese were added to the deproteinized serum obtained by acidification and warming. PH was adjusted to 4.5; the yeast was sterilized and inoculated. The maximum rate of growing for the yeast was of 0.0398 h-1 and the coefficient of biomass produced per unit of mass of substrate consumed was of 0.272. A model of screening of Placket Burman design with 11 variables was generated, resulting as the most important ones: the deproteinized serum of cheese, yeast extract and ferrous sulfate FeSO4, being the first one the most significant (p<0.05) for the obtaining of Kluyveromyces fragilis biomass.